Tyrphostin AG 490 Restored the Attenuated Cardioprotective Potential of Ischemic Postconditioning in Hyperhomocysteinemic Rat Hearts - ANKUR ROHILLA,; GURFATEH SINGH,; RAMNIK SINGH, (International Journal of Pharma and Bio Sciences, 2010)
The present study was aimed to investigate the probable role of Tyrphostin AG 490, a selective inhibitor of Janus kinase-2 (JAK-2) in hyperhomocysteinemia-induced attenuation of the cardioprotective potential of ischemic postconditioning (IPOC). Rats were administered L-methionine (1.7 g/kg/day, p.o.) for 4 weeks to produce hyperhomocysteinemia. Isolated Langendorff's perfused normal and hyperhomocysteinemic rat hearts were subjected to global ischemia for 30 min followed by reperfusion for 120 min. Myocardial infarct size was assessed macroscopically using triphenyltetrazolium chloride (TTC) staining. Coronary effluent was analyzed for lactate dehydrogenase (LDH) and creatine kinase (CK) release to assess the degree of myocardial injury. Moreover, the oxidative stress in heart was assessed by measuring lipid peroxidation and superoxide anion generation. The ischemia-reperfusion (I/R) was noted to produce myocardial injury in normal and hyperhomocysteinemic rat hearts as assessed in terms of increase in myocardial infarct size, LDH and CK in coronary effluent and oxidative stress. Hyperhomocysteinemic rat hearts showed enhanced I/R-induced myocardial injury with high degree of oxidative stress as compared with normal rat hearts. Six episodes of postconditioning (10 sec each) afforded cardioprotection against I/R-induced myocardial injury in normal rat hearts but postconditioning-mediated myocardial protection against I/R-injury was abolished in hyperhomocysteinemic rat hearts. Treatment with Tyrphostin AG 490 (5 µM) did not affect the cardioprotective effect of postconditioning in normal rat hearts; but its treatment significantly restored the cardioprotective potential of IPOC in hyperhomocysteinemic rat hearts. It is concluded that the high degree of oxidative stress produced in hyperhomocysteinemic rat hearts during reperfusion and consequent activation of JAK-2 may be responsible to attenuate the cardioprotective potential of IPOC against I/R-induced myocardial injury.